De Novo Assembly and Transcriptome Characterization of Canine Retina Using High-Throughput Sequencing. (16th December 2015) - Reddy, Bhaskar; Patel, Amrutlal K.; Singh, Krishna M.; Patil, Deepak B.; Parikh, Pinesh V.; Kelawala, Divyesh N.; Koringa, Prakash G.; Bhatt, Vaibhav D.; Rao, Mandava V.; Joshi, Chaitanya G.
Abstract : We performed transcriptome sequencing of canine retinal tissue by 454 GS-FLX and Ion Torrent PGM platforms. RNA-Seq analysis by CLC Genomics Workbench mapped expression of 10, 360 genes. Gene ontology analysis of retinal transcriptome revealed abundance of transcripts known to be involved in vision associated processes. The de novo assembly of the sequences using CAP3 generated 29, 683 contigs with mean length of 560.9 and N50 of 619 bases. Further analysis of contigs predicted 3, 827 full-length cDNAs and 29, 481 (99%) open reading frames (ORFs). In addition, 3, 782 contigs were assigned to 316 KEGG pathways which included melanogenesis, phototransduction, and retinol metabolism with 33, 15, and 11 contigs, respectively. Among the identified microsatellites, dinucleotide repeats were 68.84%, followed by trinucleotides, tetranucleotides, pentanucleotides, and hexanucleotides in proportions of 25.76, 9.40, 2.52, and 0.96%, respectively. This study will serve as a valuable resource for understanding the biology and function of canine retina.